Report of the committee appointed by the Lords Commissioners of the Admiralty to inquire into and report on the recent Arctic expeditions in search of Sir John Franklin : together with the minutes of evidence taken before the committee and papers connected with the subject. - Great Britain. Admiralty. Arctic Committee. (London : George Edward Eyre and William Spottiswoode, 1852)
"Presented to both Houses of Parliament by command of Her Majesty." Caption title: Report of the Arctic Committee. At head of title: Arctic expeditons. Mode of access: Internet.